Investigating Indonesian language varieties in social media interactions: Implications to teaching practices - Hari Bakti Mardikantoro; Muhammad Badrus Siroj; Esti Sudi Utami; Endang Kurniati (Indonesian Journal of Applied Linguistics, 2023)
Social media users come from various circles with different social and cultural statuses which will bring up diverse language variations. Additionally, language variations in speech events on social media certainly have characteristics that are distinctive and different from speech events in general. This study aimed at investigating types and forms of Indonesian language varieties occurred in speech events on social media. A quantitative and qualitative approaches was applied to accomplish the research objective. The quantitative approach was carried out using content analysis. The qualitative approach used was based on sociolinguistic theory. The research data were collected using the listening method (uninvolved conversation observation technique, recording technique, note-taking technique) and questionnaire method. The data were analyzed using the content analysis method to determine the form and percentage of language variety used in speech events on social media. In addition, Miles and Huberman's model was also used for data reduction, verification, conclusion drawing. The research found that language varieties in speech events on social media was not dominated by non-standard varieties, and inter-language mixture (code switching and code mixing). The characteristics of speech events on social media use, among others, informal language, daily-conversation language, unnatural context, and shortened writing. The results implied that the variety of language use on social media has increased since the COVID-19 pandemic. Therefore, it is necessary to research the use of codes, politeness, or hate speech on social media. Moreover, opportunities are also open to research the use of social media for language learning.